Exposure to past immigration waves and attitudes toward newcomers - Rania Gihleb; Osea Giuntella; Luca Stella (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
How does previous exposure to massive immigrant inflows affect concerns about current immigration and the integration of refugees? To answer this question, we investigate attitudes toward newcomers among natives and previous immigrants. In areas that in the 1990s received higher inflows of immigrants of German origin-so-called ethnic Germans-native Germans are more likely to believe that refugees are a resource for the economy and the culture, viewing them as an opportunity rather than a risk. Refugees living in these areas report better health and feel less exposed to xenophobia.
Keywords: A13; D64; J6; I31; 330; Immigration; Refugees; Birthplace diversity; Public Opinion; Einwanderung; Migranten; Öffentliche Meinung; Soziale Integration; Arbeitsmarktintegration; Deutschland